Adolescents' Physical Activities and Peer Norms: The Mediating Role of Self-Efficacy. Issue 2 (April 2014) - Lu, Frank J. H.; Hsu, Ya-Wen; Wang, Erica T. W.; Lin, Ju-Han; Chou, Chien-Chih; Yeh, Li-Chin
The purpose of the present study was to examine the relations among adolescents' self-efficacy and social norms, and physical activity and whether self-efficacy mediated the relationship between social norms and physical activity. 400 junior high school students (202 boys, 198 girls, 2 not identified; M age=15.3 yr., SD = 0.6) completed a demographic questionnaire, the International Physical Activity Questionnaire (IPAQ), the Perceived Self-Efficacy in Physical Activity Scale, and the Physical Activity Social Norms Scale. Regression analyses indicated that both self-efficacy and social norms predicted physical activity. Self-efficacy fully mediated the relationship between peer norms and physical activity for boys but partially mediated the relationship for girls. An application of the results may be to foster self-efficacy and peer norms as a motivational strategy for supporting increased physical activity.